The Role of Trust as an Economic Driver: The Impact of Product Quality and User Experience on Shopee Marketplace Purchases - Widyasanti, Ida Ayu Hita; Rahmawati, Putu Indah; Telagawati, Ni Luh Wayan Sayang (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine: (1) the effect of product quality on purchasing decisions, (2) the effect of ease of use on purchasing decisions, (3) the effect of trust on purchasing decisions, (4) the effect of product quality on trust, (5) the effect of ease of use on trust, (6) the mediating role of trust on the relationship between product quality and purchasing decisions, and (7) the mediating role of trust on the relationship between ease of use and purchasing decisions. The population of this study consisted of 61 fourth-semester students enrolled in the Master of Management Science Program at Ganesha University of Education. The census method was used to determine the sample, resulting in 61 participants. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that: (1) product quality has a positive and significant effect on purchasing decisions, suggesting that higher product quality on the Shopee Marketplace increases students' purchasing decisions; (2) ease of use has a positive and significant effect on purchasing decisions, indicating that greater ease of use enhances students' purchasing decisions; (3) trust positively and significantly affects purchasing decisions, meaning that higher trust in the Shopee Marketplace leads to higher purchasing decisions; (4) product quality positively and significantly influences trust, showing that better product quality increases students' trust; (5) ease of use positively and significantly influences trust, implying that easier use enhances students' trust; (6) trust partially mediates the effect of product quality on purchasing decisions, indicating that higher product quality increases trust, which in turn strengthens purchasing decisions; and (7) trust fully mediates the effect of ease of use on purchasing decisions, suggesting that greater ease of use enhances trust, thereby positively influencing purchasing decisions. These findings highlight the critical role of trust as a mediator between product quality, ease of use, and purchasing decisions in the context of the Shopee Marketplace.